Avaliação do cobre por quatro extratores químicos em solos do estado do Ceará - Costa Filho, José Hosames Ferreira (1998)
In order to compare the efficiency of four chemical extractors for copper in different kinds of soil in Ceará (BR), as well as to determine the critical levels of this element in soil and plant, a study was conducted under greenhouse conditions. The forty one samples from different soils received fertilization of two copper levels (0 and 4 mg L-1 ) . Corn (Zea mays L.) was used as the indicative plant and HC1 0,1 mol L-1 , Mehlich — 1, DTPA and AB — DTPA were used as extractors. The experimental design was totally random, with the treatments in fatorial model (41 x 2 x 3). A significant result was observed in the production of dry matter in six categories of soil , being on the average 35,44 / vase in the treatment without copper and 37, 78 g / vase in the treatment with copper. On the average the copper level and 6,1 mg kg-1 in the treatment with copper . The amount of copper by absorbed the corn was 170 mg / vase in the treatment without copper and 232 mg / vase in the treatment with copper . The correlation coefficients of the production with the extracted copper were larger in the extractors AB — DTPA (r = 0,576 *) and D1'PA (r = 0,545 *) in relation to the HC1 (r = 0,349 *) and Mehlich —1 (r = 0,383 *) denoting more efficiency in the first of the two. The average amount of copper extracted by HC1 0,1 mol L-1 was of 1,13 mg L-1 , 0,451 mol L-1 for the Mehlich — 1 , 1,0 mol L-1 for DTPA and 5,76 mol L-1 for AB — DTPA. For a relative production of 90% , the critical level of copper in the soil was 0,42 mol L-1 for DTPA; 2,87 mol L-1 for AB — DTPA; 0,46 mol L-1 for the HC1 0,1 mol L-1 and 0,18 mol L-1 for the Mehlich - 1.